Strategi Kebijakan Pemberdayaan Perempuan dan Penguatan Pembangunan Keluarga Dalam Perencanaan Pembangunan Daerah di Kabupaten Bangka Barat - Kurniasih, Dewi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Bangka Belitung Islands Province, specifically West Bangka Regency, was recorded in 2020 as having the highest rate of child marriage in Indonesia. This issue leads to problems such as domestic violence, gender inequality, and increased stunting. The prevalence of stunting in West Bangka Regency is 6.5%, with a 2024 target of 6.4%, meaning achievement is 98.43%. However, prevention has not been fully realized as new cases continue to appear. Thus, efforts must focus on reducing stunting from the source and promoting gender equality through preventive measures. One strategy in the draft Regional Medium-Term Development Plan 2025–2029 is women’s empowerment and strengthening family development, supporting the Regent’s mission of realizing welfare and socio-cultural resilience, with indicators being the Gender Inequality Index and the Family Development Index. Given difficulties in obtaining child marriage data, particularly unregistered cases, strengthening cooperation among stakeholders and pentahelix elements is essential. This paper applies a descriptive qualitative approach using Government Roles theory and policy alternative scoring based on effectiveness, efficiency, and long-term impact, while also assessing problems with the USG pattern (urgency, seriousness, growth). The aim is to provide policy recommendations for strengthening family resilience and quality. Keywords: policy strategy, women's empowerment, family development and child marriage.